The Influence of Tax Planning on Tax Optimization in Companies Listed on the Indonesia Stock Exchange (Case study of the Food & Beverage company PT Campina Ice Creamy Industry Tbk) - Sherla Winanda Putri; Ida Farida (Jurnal Riset Perpajakan: Amnesty, 2024)
This article is intended to identify the impact of tax planning strategies on efforts to optimize tax payments in companies listed on the Indonesia Stock Exchange. This research was conducted with a focus on PT Campina Ice Cream Industry Tbk, a business entity in the Food & Beverage sector. The research method includes analysis of company financial report data and a review of literature related to company information during a certain period. The research results show that the implementation of tax planning practices has a significant influence on optimizing company tax payments. Tax planning strategies not only provide meaningful financial benefits, but also increase tax efficiency and reduce corporate tax burdens. The implications of these findings can provide further understanding to company management, tax practitioners and regulators regarding the importance of effective tax planning in supporting company financial stability in the Indonesian capital market.